Coital experience among adolescents in three social-educational groups in Urban chiang mai, Thailand - Tangmunkongvorakul A. (2017)
This article compares coital experience of Chiang Mai 17-20-year-olds who were: (1) out-of-school; (2) studying at vocational schools; and (3) studying at general schools or university. Four-fifths, two-thirds and one-third, respectively, of males in these groups had had intercourse, compared to 53, 62 and 15 per cent of females. The gender difference for general school/university students, but not vocational school students, probably reflects HIV/AIDS refocusing male sexual initiation away from commercial sex workers. Vocational school females may have been disproportionately affected. Loss of virginity was associated, for both sexes, with social-educational background and lifestyle, and was less likely in certain minority ethnic groups. Among males, it was also associated with age and parental marital dissolution, and among females, with independent living and parental disharmony. Within social-educational groups, lifestyle variables dominated, but among general school/university students, parental marital dissolution (for males) and disharmony (for females) were also important, and Chinese ethnicity deterred male sexual experimentation. © 2012 Copyright Taylor and Francis Group, LLC.